2016
DOI: 10.1111/jam.13247
|View full text |Cite
|
Sign up to set email alerts
|

Reduced susceptibilities to biocides and resistance to antibiotics in food-associated bacteria following exposure to quaternary ammonium compounds

Abstract: Extensive use of DDAC at subinhibitory concentrations may lead to the development of antibiotic-resistant bacteria and may represent a public health issue.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(35 citation statements)
references
References 17 publications
0
32
1
1
Order By: Relevance
“…Soumet et al . ) found increased MIC values for several antibiotics including chloramphenicol—but also ceftazidime—after adaption to DDAC.…”
Section: Discussionmentioning
confidence: 99%
“…Soumet et al . ) found increased MIC values for several antibiotics including chloramphenicol—but also ceftazidime—after adaption to DDAC.…”
Section: Discussionmentioning
confidence: 99%
“…Adaptive responses of bacterial strains were investigated by the daily exposure of the tested isolates to incremental increases in sublethal concentrations of TCS according to the method described by Soumet et al (2016). Experiment starting with concentration of 0Á59 MBC of TCS.…”
Section: Adaptation To Increasing Concentrations Of Tcsmentioning
confidence: 99%
“…In exposure experiments under laboratory conditions, it has been shown that stepwise repeated exposure of susceptible bacteria to subinhibitory concentrations of disinfectants may lead to decreased susceptibility to various antimicrobial agents [13][14][15][16][17]. However, many of these investigations do not relate such findings to practical conditions and the laboratory results are not necessarily relevant to agricultural environments.…”
Section: Introductionmentioning
confidence: 99%